Retinoic acid‐induced autoantigen‐specific type 1 regulatory T cells suppress autoimmunity. (20th March 2019) - Raverdeau, Mathilde; Christofi, Maria; Malara, Anna; Wilk, Mieszko M; Misiak, Alicja; Kuffova, Lucia; Yu, Tian; McGinley, Aoife M; Quinn, Shauna M; Massilamany, Chandirasegaran; Reddy, Jay; Forrester, John V; et al.
Abstract: Regulatory T (Treg) cells help to maintain tolerance and prevent the development of autoimmune diseases. Retinoic acid (RA) can promote peripheral conversion of naïve T cells into Foxp3 + Treg cells. Here, we show that RA can act as an adjuvant to induce antigen‐specific type 1 Treg (Tr1) cells, which is augmented by co‐administration of IL‐2. Immunization of mice with the model antigen KLH in the presence of RA and IL‐2 induces T cells that secrete IL‐10, but not IL‐17 or IFN‐γ, and express LAG‐3, CD49b and PD‐1 but not Foxp3, a phenotype typical of Tr1 cells. Furthermore, immunization of mice with the autoantigen MOG in the presence of RA and IL‐2 induces Tr1 cells, which suppress pathogenic Th1 and Th17 cells that mediate the development of experimental autoimmune encephalomyelitis (EAE), an autoimmune disease of the CNS. Furthermore, immunization with a surrogate autoantigen, RA and IL‐2 prevents development of spontaneous autoimmune uveitis. Our findings demonstrate that the induction of autoantigen‐specific Tr1 cells can prevent the development of autoimmunity. Synopsis: Immunization of mice with an autoantigen, formulated with retinoic acid and IL‐2 as adjuvants, promotes the induction of antigen‐specific type 1 Tregs (Tr1). These Tr1 cells prevent autoimmunity mediated by Th1 and Th17 T cells. Retinoic acid and IL‐2 act as adjuvants for the induction of Tr1 cells in mice. Induced autoantigen‐specific Tr1 cells suppress Th1 and Th17 cells that mediate autoimmune disease. Immunization with an autoantigen in the presence of RA and IL‐2 suppresses EAE and autoimmune uveitis. Abstract : Immunization of mice with an autoantigen, formulated with retinoic acid and IL‐2 as adjuvants, promotes the induction of antigen‐specific type 1 Tregs (Tr1). These Tr1 cells prevent autoimmunity mediated by Th1 and Th17 T cells.